ARCHITECTURE AFTER GRAVITY: UNDERSTANDING SPATIAL EXPERIENCE OF WEIGHTLESSNESS AND DISORIENTATION - Elawati, Ocfia Amirul; Paramita, Kristanti Dewi; Atmodiwirjo, Paramita (MODUL, 2024)
This study examine the idea of after gravity as the basis of an architectural design method. After gravity is defined as the condition of weightlessness and disorientation that creates unrestricted body movement. Gravity determines the direction of architectural spatial orientation and gives weight to subject and object in architectural space, creating boundaries of possible body movements. This paper analyzes the development of a design method based on that appropriates gravity through the analytical study of ten gravity-defying body movements such as hanging, flying, or spinning. The study identifies three gravity-based relations; happening between bodies, between body and object, and between body and space. The design method of architecture after gravity highlights the spatial experience of the moving body in receiving stimuli and responding to the context. Understanding architecture after gravity widens the potential of architecture that sees the relations of forces in a context with the body in a dynamically built environment.